Evaluating the safety and effectiveness of a nurse-led outpatient virtual IV vancomycin monitoring clinic: a retrospective cohort study. Issue 1 (18th January 2021) - Grattan, Kate S; Mohamed Ali, Mohamed; Hosseini-Moghaddam, Seyed M; Gilmour, Hayley J I; Crunican, Gregory P; Hua, Erica; Muhsin, Kelly A; Johnstone, Rochelle; Bondy, Lise C; Devlin, Megan K; Shalhoub, Sarah; Elsayed, Sameer; et al.
Abstract: Background: Outpatient parenteral antimicrobial therapy (OPAT) with vancomycin is a common treatment modality for certain Gram-positive infections. Data regarding the safety of various models of delivery are limited. Objectives: To review outcomes of a nurse-led OPAT vancomycin monitoring service. Methods: This was a retrospective cohort study of consecutive patients referred to a nurse-led OPAT vancomycin clinic from December 2015 to March 2018. Patients were administered IV vancomycin in the home with active laboratory monitoring of vancomycin trough levels, renal function and complete blood count using an integrated electronic database linked with community laboratories (virtual vancomycin clinic, VVC). Monitoring was coordinated by nurses with physician approval of recommended dosing changes. Data were extracted from the electronic medical record. Demographics; clinical indication; microbial aetiology; culture source; antimicrobial regimen(s); serum creatinine and vancomycin trough values; initiation, discharge and completion dates; hospitalizations; adverse events; and outcomes were all evaluated. Results: Two hundred and seventy-five patients underwent a total of 301 courses of OPAT with vancomycin; 285 courses were completed. The rate of treatment discontinuation due to adverse effects was 33/301 (11.0%), with 15/33 (45.5%) being due to renal adverse effects (15/301 [5.0%] of episodes). Two of 15 (18.2%) patients developed stage 2 acute kidney injury (AKI), and no patients had stage 3 AKI or required haemodialysis. Nine of 301 (3.0%) required readmission for treatment failure. Nursing costs associated with monitoring were 63.93 CAD/patient (48.43 USD). Conclusions: A nurse-led VVC was a safe, effective and inexpensive modality for administering outpatient vancomycin.